Method of Assessing Skin Cancerization and KeratosesTM (MASCK™): development and photographic validation in multiple anatomical sites of a novel assessment tool intended for clinical evaluation of patients with extensive skin field cancerization. (1st June 2022) - Baker, Christopher; James, Amelia; Supranowicz, Madeleine; Spelman, Lynda; Shumack, Stephen; Cole, Judith; Weightman, Warren; Sinclair, Robert; Foley, Peter
Summary: Background: A range of 'field‐directed' treatments is available for the management of extensive skin field cancerization (ESFC), but to date, the only validated objective quantitative tools are limited to assessment of actinic keratoses (AKs) affecting the head. Aims: To develop a versatile quantitative instrument for objective clinical assessment of ESFC and perform initial internal validation across multiple anatomical zones. Methods: The study comprised instrument development, pilot testing and instrument refinement and two rounds of reliability and inter‐rater validation testing. The study was noninterventional and used a convenience sample of de‐identified patient photographs selected based on preset criteria. An expert panel developed the instrument and scoring system via a modified Delphi voting process. A sample of 16 healthcare professionals from multiple specialties undertook the pilot testing, and a panel of seven dermatologists were involved in validation testing. Validation was determined by assessment of overall inter‐rater agreement using Gwet chance‐corrected agreement coefficients (ACs). Results: The instrument produced, called the Method for Assessing Skin Cancer and Keratoses™ (MASCK™), comprises the Skin Field Cancerization Index (SFCIndex), derived from area of skin involvement and AKs (number and thickness), a global assessment score and a cancer‐in‐zone score, and uses Likert scales for quantitative scoring. The SFCIndex is a composite score comprising the number and thickness of AKs multiplied by area of skin involvement. ACs for the SFCIndex components, the overall SFCIndex score and the global assessment score were > 0.80 (rated 'almost perfect') while the AC for the cancer‐in‐zone metric was lower (0.33, rated 'fair'). Internal consistency was demonstrated via positive correlation between the overall SFCIndex score and the global assessment score. Conclusions: Our study found near‐perfect agreement in inter‐rater reliability when using MASCK to assess the severity of ESFC in multiple anatomical sites. Further validation of this novel instrument is planned to specifically assess its reliability, utility and feasibility in clinical practice. Abstract : The current assessment of extensive skin field cancerization (ESFC) is largely subjective. We report a new scale, the Method for Assessing Skin Cancerization and Keratoses (MASCK™), which comprises the Skin Field Cancerization Index (derived from number and thickness of actinic keratoses and area of skin involvement), a global assessment score and a cancer‐in‐zone score, and uses Likert scales for quantitative scoring. Initial validation data are presented, demonstrating near‐perfect inter‐rater agreement when using MASCK to assess the severity of ESFC in multiple anatomical sites.